Interrogating Canonical World English Literature: Journey to the West and Romance of the Three Kingdoms - Kristiawan Indriyanto (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2017)
This paper aims to chart how literary work of non-Western origin is incorporated into World English Literature by giving example of two Chinese Classic Novels. Among the Chinese Classic Novels, Journey to the West is the novel that achieves wider popularity among West- ern scholars and canonized while other Chinese Classic Novels are not as popular especially among Western academia. The different reception is related also with how both novels are circulated, translated, and adapted from Chinese into English. The emphasis of this paper is to compare the issue of circulation, translation, and adaptation between Journey to the West and Romance of the Three Kingdoms as another Chinese Classic Novel. By comparing differ- ent issues of how both novels enter the Western World, this paper hopes to have an insight regarding how these two novels have different popularity among academic scholars.